Optimalisasi Kenyamanan Termal pada Gedung Sekolah Menengah Atas di Kota Pontianak melalui Pendekatan Arsitektur Tropis - Meladita Eka Adrila; Endah Tisnawati (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2025)
Pontianak City, which has a tropical humid climate, faces challenges in creating a comfortable learning environment due to the high temperatures and humidity throughout the year. This scientific paper aims to explain the concept of designing a Senior High School (SMA) building in Pontianak City using a tropical architecture approach that can optimise thermal comfort for its occupants. This design applies tropical architecture principles by considering building orientation, utilising natural ventilation and lighting, and using suitable materials to mitigate excessive heat and humidity. Additionally, green open spaces and solar radiation control are integrated to create a healthy and energy-efficient environment. The zoning of spaces is also designed to support the comfort and productivity of students, teachers, and educational staff. The design of this school is expected to provide an idea of a school design model that applies thermal comfort optimisation for users, creating a comfortable learning environment that supports sustainability in the tropics area.